Badania poziomu jakości usług medycznych na przykładzie zakładów podstawowej opieki zdrowotnej powiatu jeleniogórskiego - Januszewska, Małgorzata; Przeorek-Smyka, Renata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article tries to estimate the level of medical treatment done by health service centres. It shows the range of medical treatment quality and criterion of their estimation. The presentation of research results, which contain measurement of medical treatment valuation in Jelenia Góra district, is completed with theoretical speculations. The conducted research reveals that monitoring factors influancing the level of health centres service and the satisfaction of their clients has its reflexion in measurable benefits for a number of companies on the market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 120-131